Langues et cultures régionales, langues vivantes étrangères Quels enjeux pour une convergence didactique ? - James Costa (Recherches en didactique des langues et des cultures)
In ecolinguistic terms, a school, whether primary or secondary, can be defined as an ecology within a larger ecology. Some languages are spoken, others are taught, some are both spoken and taught. Languages with various social statuses (or rather their speakers and teachers) live side by side on a daily basis.Yet some schools add a specific dimension to their ecolinguistic setting, i.e. schools that are located in areas where a minority language is or used to be spoken. Once taught, the minority language becomes part of the ecology, even though none of the pupils who chose it as a subject might have it as first language. Most other language teachers in France usually choose to ignore that fact, and little collaboration actually takes place between teachers of minority languages and teachers of foreign languages. We would like to suggest that both teachers of foreign languages and teachers of French are thereby depriving themselves of potentially valuable resources.